Coordination dynamics of back-and-forth movement among expert performers: interaction in the battle scene of breaking - Shimizu, Daichi; Okada, Takeshi (Frontiers in Psychology, 2025)
Complex interactions are central to the performing arts. While recent studies have explored these dynamics through synchronization and coordination theories, they have mainly focused on collaborative contexts. In contrast, genres like jazz sessions and breaking battles involve active competition, where performers seek to outshine one another. Although prior research has identified patterns like anti-phase synchronization in such settings, coordination across expressive channels and differences from sports interactions remain underexplored. To address this gap, the present study had two objectives: first, to investigate coordination through back-and-forth movements during breaking battles, and second, to compare these patterns with those observed in interpersonal sports. We conducted an experimental study simulating a battle scene with expert break dancers, examining how they coordinated their movements and managed relative distances. The results revealed two key findings: (1) dancers maintained close distances (~1.0 m) while coordinating through anti-phase synchronization (−180° to −160° and 160° to 180° relative phases), with coordination patterns shifting dynamically—from leader-follower relationships to anti-phase and then in-phase synchronization—depending on context and time; and (2) such time- and context-dependent coordination dynamics were unique to the performing arts and not observed in interpersonal sports. This study highlights the distinctive nature of context-sensitive, multi-channel interpersonal coordination in competitive performing arts.